Investigation of the health status of Michigan chemical corporation employees. - Anderson, H A (1978)
Clinical findings are reported for a group of 55 employees of the Michigan Chemical Corporation which manufactured FireMaster BP-6 from 1970 to 1974, in addition to a variety of other halogenated fire retardant chemicals. The results are compared with those from a group of male farm residents and consumers from Michigan examined at the same time. An increased prevalence of chest and skin symptoms was observed, compared with farmers. Skin symptoms were more prevalent among former PBB production personnel. Musculosketal symptoms were less prevalent among these workers than among farmers. Serum PBB concentrations are signicantly higher than among farmers. Blood chemistry results were similar for workers and farmers. However, both groups exhibited a significantly higher prevalence of elevated liver function tests (SGOT, SPGT) than a control population of nonexposed farmers. Both farmers and chemical workers showed an association of elevated CEA with serum PBB greater than 10 ppb.